Critical thinking skills of undergraduate students of educational sciences at Tehran universities - NICKNAME, Z; ROYAFAR, A. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThe present study aims to investigate the critical thinking skills of students in the educational sciences of Tehran universities. The population of study is undergraduate students of educational sciences of Tehran universities and the sample is 200 students of educational sciences selected using the stratified random sampling method. Data were collected using the California Critical Thinking Skills Test and analyzed using the one-sample t-test and multivariate analysis of variance. The results showed that the total score of critical thinking among undergraduate students of educational sciences was lower than the assumed mean value.RESUMENEl objetivo del presente estudio es investigar las habilidades de pensamiento crítico de los estudiantes de ciencias educativas de las universidades de Teherán. La población del estudio son estudiantes universitarios de ciencias educativas de las universidades de Teherán y la muestra es de 200 estudiantes de ciencias educativas seleccionados mediante el método de muestreo aleatorio. Los datos se recolectaron usando la prueba (CCTS) y se analizaron usando la prueba t de una muestra y el análisis de varianza multi-variante. Los resultados mostraron que la puntuación total del pensamiento crítico entre los estudiantes universitarios de ciencias de la educación fue inferior al valor medio supuesto.